A Case of Complete Chorioamniotic Membrane Separation after Amniocentesis Resulted with a Healthy Term Delivery - Tuğba Altun Ensarı; Oya Aldemir; Bülent Yırcı; Sertaç Esin; Serdar Yalvaç; Ömer Kandemir (Medical Network, 2016)
Separation between amniotic and chorionic membranes is a normal sonographic finding before 14th weeks of gestation. As pregnancy progresses, these membranes fuse and chorionic cavity becomes obliterated. Chorioamniotic membrane separation may occur spontaneously or as a complication of invasive intrauterine procedures. Following invasive fetal intervention, resulting in a condition referred to as chorioamniotic membrane separation (CMS) and it is reported to be associated with adverse perinatal fetal outcomes. Here we present a case of CMS that had occurred after a second trimester amniocentesis and resulted with the delivery of a term healthy baby. Complete post-interventional CMS may complicate pregnancy progression. Although there are no established guidelines to follow, close follow-up may CMS can be managed to be a morbid, rather than mortal condition.